2021
DOI: 10.3390/ijms23010037
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Sensor AMPKα1 Is Critical in Rapamycin-Inhibition of mTORC1-S6K-Induced T-cell Memory

Abstract: Energy sensors mTORC1 and AMPKα1 regulate T-cell metabolism and differentiation, while rapamycin (Rapa)-inhibition of mTORC1 (RIM) promotes T-cell memory. However, the underlying pathway and the role of AMPKα1 in Rapa-induced T-cell memory remain elusive. Using genetic and pharmaceutical tools, we demonstrate that Rapa promotes T-cell memory in mice in vivo post Listeria monocytogenesis rLmOVA infection and in vitro transition of effector T (TE) to memory T (TM) cells. IL-2- and IL-2+Rapa-stimulated T [IL-2/T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Our data collectively indicate that IL-15/mTORC1 Weak signaling induces T M -cell formation in IL-15/T M cells via activation of the transcriptional FOXO1-TCF1 Eomes and metabolic AMPK-ULK1-ATG7 pathways while IL-2/mTORC1 Strong signaling promotes T E -cell differentiation in IL-2/T E cells via activation of the transcriptional T-bet and metabolic HIF-1α pathways ( Figure 6 A). These findings represent a novel molecular mechanism for T-cell memory in the LCD model [ 4 ], and are consistent with our recent reports showing that the pro-survival cytokine IL-7 or an inflammatory IL-2/rapamycin combinatorial treatment triggers mTORC1 Weak signaling to promote T-cell memory via the same transcriptional FOXO1 and metabolic AMPKα1 pathways [ 18 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our data collectively indicate that IL-15/mTORC1 Weak signaling induces T M -cell formation in IL-15/T M cells via activation of the transcriptional FOXO1-TCF1 Eomes and metabolic AMPK-ULK1-ATG7 pathways while IL-2/mTORC1 Strong signaling promotes T E -cell differentiation in IL-2/T E cells via activation of the transcriptional T-bet and metabolic HIF-1α pathways ( Figure 6 A). These findings represent a novel molecular mechanism for T-cell memory in the LCD model [ 4 ], and are consistent with our recent reports showing that the pro-survival cytokine IL-7 or an inflammatory IL-2/rapamycin combinatorial treatment triggers mTORC1 Weak signaling to promote T-cell memory via the same transcriptional FOXO1 and metabolic AMPKα1 pathways [ 18 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that active β-catenin molecules transported into the nucleus stimulate the expression of its down-stream transcription factors TCF1 and LEF in the nucleus for OBD [ 7 ]. To measure the β-catenin localization, the MC3T3-E1 cells cultured under µg and 1-g conditions were stained with DAPI for nuclear (blue) and FITC-labeled anti-β-catenin antibody for β-catenin (green), and then measured by confocal microscopy [ 20 , 21 ]. We demonstrated that significantly more β-catenin molecules were found in the nuclei of the MC3T3-E1 cells cultured under 1 g condition compared to the MC3T3-E1 cells under µg condition ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were then incubated with FITC-rabbit anti-β-catenin antibody (green) (1:100) for staining of β-catenin in 1% BSA for 2 h in dark at room temperature. After rinsing cells three times with PBS, the slides were covered with Prolong Gold Antifade Reagent with DAPI (blue) for staining of nuclei and checked by confocal microscopy [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…AMPK is a regulator of FAO and glycolysis and the inability to generate memory T cells in AMPK-deficient mice is associated with deficient mitochondrial FAO [21]. Similarly, AMPK deficient CD8 + T cells are enable to generate memory CD8 + T cells [96][97][98][99]. In summary, metabolism signature of memory T cells remains uncertain while they exhibit an elevated profile of glycolysis and OXPHOS.…”
Section: Memory T Cellsmentioning
confidence: 99%